Reliable blood cancer cells' telomere length evaluation by qPCR. (6th March 2020) - Ropio, Joana; Chebly, Alain; Ferrer, Jacky; Prochazkova‐Carlotti, Martina; Idrissi, Yamina; Azzi‐Martin, Lamia; Cappellen, David; Pham‐Ledard, Anne; Soares, Paula; Merlio, Jean‐Philippe; Chevret, Edith
Abstract: Background: Telomere shortening is linked to a range of different human diseases, hence reliable measurement methods are needed to uncover such associations. Among the plethora of telomere length measurement methods, qPCR is reported as easy to conduct and a cost‐effective approach to study samples with low DNA amounts. Methods: Cancer cells' telomere length was evaluated by relative and absolute qPCR methods. Results: Robust and reproducible telomere length measurements were optimized taking into account a careful reference gene selection and by knowing the cancer cells ploidy. qPCR data were compared to "gold standard" measurement from terminal restriction fragment (TRF). Conclusions: Our study provides guidance and recommendations for accurate telomere length measurement by qPCR in cancer cells, taking advantage of our expertise in telomere homeostasis investigation in primary cutaneous T‐cell lymphomas. Furthermore, our data emphasize the requirement of samples with both, high DNA quality and high tumor cells representation. Abstract : In this original article we aimed to validate the applicability of qPCR when assessing telomere length in cancer cells, taking advantage of our expertise on telomere homeostasis investigation in primary cutaneous T‐cell lymphomas